A Danish Version of the Friendship Scale: Translation and Validation of a Brief Measure of Social Isolation - Kent, Peter; Hawthorne, G.; Kjaer, P.; Manniche, C.; Albert, H. (Springer Netherlands, 2015)
Low back pain (LBP) is common and social isolation is both a risk factor for poor recovery from LBP and a consequence of LBP. The Friendship Scale is a brief measure of social isolation that has been validated for use in the general population and in people with LBP. The aim of this study was to translate, culturally adapt and validate the Friendship Scale into Danish. Translation of the English version of the Friendship Scale was performed independently by professional translators and overseen by an expert team. The Danish version was initially tested for face validity in a sample of 44 LBP patients. Subsequently, validity was examined through factor analysis, internal consistency, sensitivity by known groups and Rasch analysis in a sample of 382 Danish adult patients with LBP attending a secondary care spine centre and a general population sample of 293 people. Construct validity was examined by the relationship between Friendship Scale classification scores and study group membership and pain level. A linguistically accurate translation was achieved and no hesitation or ambiguity was observed in people completing this version. The psychometric properties of the Danish version were very similar to those found in the original version. This Danish translation of the Friendship Scale appeared to be easily understood by Danish people and has similar performance characteristics to the original version. These data indicate it has validity for use in Danish people seeking care for spinal pain and also for use in the general population.